Metode Sosio-Historis Abdullah Saeed dalam Penafsiran Ayat Waris: Studi Kritis: The Socio-Historical Method of Abdullah Saeed in Interpreting the Verse of Inheritance: A Critical Study - Ahmad Syarif Mas'ud (Center of Islamic and Occidental Studies, 2024)
In interpreting Qur'anic verses, contemporary Muslim thinkers usually argue that the present situation and the context in which the verse was revealed are different. This necessitates a new method to produce contemporary Islamic laws that are different from the Islamic laws of the past. One of them is the law of inheritance. Abdullah Saeed believes that the inheritance law that has been used since the past is no longer in accordance with today's conditions. Many women are now economically independent and have access to education and employment opportunities. By looking at this difference in conditions, Saeed proposes the idea of re-reading the inheritance verse, and then replacing the law with other possibilities. Saeed's method contradicts the tafsir methods of the pious Salaf scholars. Therefore, this article explains, analyses, and critically examines the socio-historical method offered by Abdullah Saeed in interpreting the verse of inheritance. The article finds that Saeed's attempt causes changes in meaning because interpretations will continue to change in accordance with the changing times. Changes are not only made to relative verses (mutaghayyirāt), but also to absolute verses (tsawābit). Furthermore, this socio-historical model of interpretation changes the structure of the Islamic religion, including inheritance.